(untitled) (Journal of Fatima Jinnah Medical University, 2024)
Background: Birth spacing and birth order are significant factors affecting child health and nutritional status but it is often overlooked when dealing with child undernutrition. There remains a need to consider the modifiable risk factors for undernutrition among children. Therefore, this study aimed to find the relationship of preceding birth interval and birth order with undernutrition among children under five years of age. Subjects and methods: The cross-sectional analytical study included 133 pairs of mothers and children who attended Sir Ganga Ram Hospital, Lahore, Pakistan from July to September 2023. Interviewer administered close-ended questionnaire used to collect data (characteristics of index children and their mothers). Children were categorized into well-nourished and undernourished (wasted, stunted or underweight) using the WHO standards for child growth. Crosstabs and binary logistic regression analysis were done to find the relationship between preceding birth interval, birth order and nutritional status. Results: With 67 (50.4%) boys and 66 (49.6%) girls, the mean age of children was 17.9±12.7 (range 6-59 months). Among 94 (70.7%) undernourished children, 80(85.1%) had all three indicators of undernutrition (wasting, stunting, and underweight). Birth order of the index child, age of child, family income and mother’s BMI showed significant association with childhood undernutrition (all p-values ≤0.05). Whereas preceding birth interval, contraception knowledge and practices were not related to childhood undernutrition (all p-values >0.05). Conclusion: The child’s birth order, age, family income, and maternal BMI showed significant association and greater risk of undernutrition; however preceding birth interval was not related with undernutrition among children under five. Limiting the number of births and improving maternal health and nutrition may reduce child malnutrition.